SEXUALITY CONSTRUCTION IN CINDERELLA STORY: ASH NOVEL - Nafisa Zafira Taufik; Eva Leiliyanti (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2020)
ABSTRACT Recently, there has been a huge increase of sexuality construction studies in literature field including in Young Adult genre. Ash novel is one of young adult genre retelling the classic fairy tale story of Cinderella with the gendering plot twist of the main female character. Instead of construct the main characters to heterosexual, Malinda Lo deconstructs her gender and sexual identity. The aim of this research will focuses on investigating the relationship between the elements of psychosexual development and sexuality construction in the narratives that change the main character’s gender and sexual identity. This research are using 5 stages of development theory by Sigmund Freud and performativity theory by Judith Butler. To analyze the narratives, this research is using deconstruction theory by Jaques Derrida as methodology approach. The gendering process and sexuality construction to lesbian appears in several events that bring the main character questioning the masculine role and construct her identity by the dominant stepmother. Keywords: Sexuality Construction; Cinderella; Young - Adult Literature; Lesbian; Psychosexual Development; Performativity, Deconstruction.